If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = 9x + 8 Reorder the terms: -8 + 6x = 9x + 8 Reorder the terms: -8 + 6x = 8 + 9x Solving -8 + 6x = 8 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -8 + 6x + -9x = 8 + 9x + -9x Combine like terms: 6x + -9x = -3x -8 + -3x = 8 + 9x + -9x Combine like terms: 9x + -9x = 0 -8 + -3x = 8 + 0 -8 + -3x = 8 Add '8' to each side of the equation. -8 + 8 + -3x = 8 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 8 + 8 -3x = 8 + 8 Combine like terms: 8 + 8 = 16 -3x = 16 Divide each side by '-3'. x = -5.333333333 Simplifying x = -5.333333333
| 6x-8=10x-10 | | 336/2*60-18+25 | | (2x-a)+b=3x-a | | 3.5(x-8/4)=2.8 | | 22x+3=41 | | 9/2-7=9/2 | | 27-6n=15 | | 0.75W+8=0.33W-7 | | 3v-7=1 | | 4(x+3)-2=14 | | 500+y=20000 | | 18t^2=0 | | 1/5k+15 | | 4(2*7)=2x+22+3(2*2) | | 21=8lnx | | -7x+2(-3x-5)=-16-7x | | y=(9-7k)x | | 6x+4(2x+11)=198 | | 6x+x+-2+x= | | (3b^2+2b-6)/(b-2) | | 1/2(10x-7)=4 | | 5x+3(x+11)=81 | | y+12=23 | | 98*24/4+510-60 | | 9k-1=1k-25 | | 3x+7(x-15)=-5 | | 898*6/2-25+200 | | 16x=10-(-6) | | x^2+y^2+8x-12y-29=0 | | ((-7x+23)/(x-3)^2)+(4/(x-3))+1=0 | | 4(n-2/n) | | 7x=-3y-12 |